PERAN PENDIDIKAN PRA-SEKOLAH DAN TENAGA PENDIDIK PENDIDIKAN DASAR DALAM PEMBANGUNAN KARAKTER SISWA - Ela Nurmala (STKIP Subang, 2016)
Globalization brings forth huge changes in the workplace. Profession and work specification become more delicate than ever. Education is responsible in providing qualified human resources to answer those challenges. One of the most important parts of education is character education. Character determines the future of a person, society and nation. A nation fails to pass it core values will most likely to perish. This makes character education the most important responsibility of elementary education in our nation. This paper also examines the role of pre-school education in determining student’s achievement in elementary school and current pre-schools condition in our nation. The findings suggest that first, teacher education, teacher knowledge, skill, competence and integrity positively affect effective learning process including character education and graduate quality. Second, in this nation the participation level to attend pre-school which have positive effect on student’s achievement in elementary school is still very low. The main reasons are because most people didn’t aware yet that pre-school is important and the fee needed to access pre-school is still too high for some people. We need to educate our teachers in order to understand the importance of character education and be able to accomplish it. Strategic plan is also vital to ensure the education development. We also need to socialize pre-school to the society in order to encourage them to bring their children to participate in pre-school education.